Leadership and Management Skills Impacting Sports Educators' Performance in Higher Education Institutions - Zohaib Hassan Sain; Amir Karimi (Indonesian Journal of Sport Management and Physical Education, 2023)
This study investigates how sports educators' leadership and management skills impact their performance in higher education institutions in Pakistan. A cross-sectional survey was conducted with 300 sports educators to collect the data. Descriptive statistics, Pearson correlation, and multiple regression analysis were utilized to analyze the findings. The results indicated a strong positive correlation (r = 0.72, p < 0.01) between leadership skills and performance, identifying leadership as the most significant predictor of educator success (β = 0.58, p < 0.001). Furthermore, the reliability of the scales was confirmed by high Cronbach's alpha values (α = 0.87, 0.82). This study underscores the importance of developing leadership skills among sports educators to enhance program effectiveness and improve student outcomes.